2022
DOI: 10.3389/fvets.2022.802051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catalase on Growth Performance, Antioxidant Capacity, Intestinal Morphology, and Microbial Composition in Yellow Broilers

Abstract: The objective of this experiment was to study the effects of catalase (CAT) on growth performance, antioxidant capacity, intestinal morphology, and microbial composition of yellow broilers. Male Lingnan yellow broilers (360), aged 1 day, were randomly divided into control group (CON) (fed with a basic diet), R1 group (fed with basic diet + 150 U/kg catalase), and R2 group (fed with basic diet + 200 U/kg catalase). Each group had 8 replicates and 15 chickens in each replicate. The test is divided into the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 110 publications
2
5
1
Order By: Relevance
“…In this study, dietary DON fortification at a subclinical level (an estimate of 7 mg/kg) caused little compromise of broiler growth performance except for a decreasing trend of ADFI. Supplemental CAT failed to improve growth performance of broilers exposed to DON, which did not agree with the study of Tang et al [14] who found increases in weight gain, feed intake and feed efficiency of non-challenged broilers in response to CAT addition. The discrepancy might be due to the difference in raising condition of broilers.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…In this study, dietary DON fortification at a subclinical level (an estimate of 7 mg/kg) caused little compromise of broiler growth performance except for a decreasing trend of ADFI. Supplemental CAT failed to improve growth performance of broilers exposed to DON, which did not agree with the study of Tang et al [14] who found increases in weight gain, feed intake and feed efficiency of non-challenged broilers in response to CAT addition. The discrepancy might be due to the difference in raising condition of broilers.…”
Section: Discussioncontrasting
confidence: 86%
“…These results highlighted that exogenous CAT was beneficial for attenuating DON-induced oxidative stress in broilers. Likewise, some previous studies reported that dietary CAT addition improved redox status by enhancing the activities of antioxidant enzymes (SOD, CAT, and GSH-Px) and lowering oxidative metabolite MDA in the liver and intestine of both broilers [14] and pigs [16].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations